2017
DOI: 10.1016/j.tim.2017.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Black Truffle, a Hermaphrodite with Forced Unisexual Behaviour

Abstract: The life cycle of the black truffle (Tuber melanosporum) includes a mating before sporulation: although the species is hermaphroditic, mating turns out to involve parents with very different features, that mostly behave as male or female only, suggesting that this species undergoes forced dioecism

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 12 publications
2
29
0
Order By: Relevance
“…This condition was also confirmed in T. melanosporum (Riccioni et al, 2008;Rubini et al, 2011a) and T. borchii , indicating that heterothallic life style is common within the Tuber genus and fruiting body production depends on the mating between mycelia harbouring different mating types. Mycelia of both mating types can act as a maternal partner, indicating hermaphroditism (Selosse et al, 2017). The haploid maternal genotype of truffles forms the sterile tissues of the fruiting body, and it is fed from the surrounding mycorhizas throughout the maturation time (Rubini et al, 2011a;Le Tacon et al, 2013;Murat et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This condition was also confirmed in T. melanosporum (Riccioni et al, 2008;Rubini et al, 2011a) and T. borchii , indicating that heterothallic life style is common within the Tuber genus and fruiting body production depends on the mating between mycelia harbouring different mating types. Mycelia of both mating types can act as a maternal partner, indicating hermaphroditism (Selosse et al, 2017). The haploid maternal genotype of truffles forms the sterile tissues of the fruiting body, and it is fed from the surrounding mycorhizas throughout the maturation time (Rubini et al, 2011a;Le Tacon et al, 2013;Murat et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In the field, T. melanosporum displays a strong genetic isolation with strains of opposite mating types spatially confined in separate patches in which a few dominant genotypes can persist throughout the years (Rubini et al, 2011b;Taschen et al, 2016;De la Varga et al, 2017). Due to the important turnover and small spatial size of the paternal genotypes, it has been suggested that in most cases germinating ascospores could act as a paternal partner (Selosse et al, 2013;Le Tacon et al, 2016;Taschen et al, 2016;De la Varga et al, 2017;Selosse et al, 2017). However, this hypothesis remains to be demonstrated, and the nature of the paternal genotype is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…‘male-male competition’ and ‘female choice’, also apply to fungi [15,16]. In many groups of fungi, different sex roles can be distinguished [1719], which can result in different phenotypes [20], and there is a skew between the number of fertilizing individuals and individuals to be fertilized [21]. We have previously demonstrated that there is genetic variation in competitive ability and in choice between fungal individuals during mating [15].…”
Section: Introductionmentioning
confidence: 99%
“…They reported that each DNA sample of T. melanosporum analyzed displayed the presence of either the MAT1-2 or the MAT1-1 idiomorph. Previous studies indicated that although black truffle spores of both mating types coexisted on young seedlings, one of the mating types was progressively supplanted over time [ 32 ]. These findings are consistent with the results of this study, which showed that in natural-truffle-producing-areas, the MAT1-2-1 gene could be detected in only three of the collected soil samples (Ti-S-3, Ti-S-4, and Ti-S-6), suggesting that the MAT1-1-1 gene may be excluded over time.…”
Section: Discussionmentioning
confidence: 99%